Formulation and Evaluation of Face Mist Preparations from Plant Extracts: A Literature Review - Elsa Oktavia Angelica; Eliah Herawati; Melisa Puspitasari; Nia Yuniarsih (Archives of The Medicine and Case Reports, 2022)
Face mist is a skin care product containing a liquid that can be sprayed on the facial skin. The preparation of face mist preparations is carried out starting from the extraction process, followed by the process of making face mist, and finally, the evaluation of the preparation. In making face mist, several testing conditions must be carried out, namely organoleptic test (including shape, color, and odor), spray dispersion test, viscosity test, skin irritation test, specific gravity, facial moisture, pH test, and dry time test. Some plants have been tested or formulated in the form of face mist preparations, namely aloe vera, cucumber, honey, yam, purple cabbage, and apple skin. This literature review aims to discuss various formulations and preparations of face mist from plant extracts.